Remote sensing and GIS approach for estimation of water spread area of surface waters of Srinagar city in Kashmir Himalayan region - MARYAM, MUNJID; KUMAR, ROHITASHW (Journal of Soil and Water Conservation, 2026)
The present study quantifies decadal changes (2000–2020) in the water spread area of Srinagar’s major surface waters (Dal Lake, Nigeen Lake, Anchar, Gilsar–Khushalsar, Brari Nambal, Nallah Amir Khan, Jhelum River) using multi temporal LANDSAT imagery and ASTER GDEM. Imagery was atmospherically corrected (Dark Object Subtraction) and geometrically aligned; water bodies were delineated via normalized difference water index (NDWI) with a threshold of ≥0.3, and refined by MNDWI to reduce built up misclassification. Supervised maximum likelihood classification and Otsu thresholding were applied; overall accuracy and Kappa coefficient were assessed against high resolution reference points (n=150), yielding 92.4% accuracy and κ=0.89. Results show a 21.5% average decline in lake and wetland area, with the steepest loss in Brari Nambal (41%) and modest recovery in Dal Lake (+1.9%) post 2014 flood remediation. Correlation with long term precipitation and built up area expansion (derived from 2000–2020) indicates strong links (r=0.78, p